Horizontal ecological compensation and urban resilience: mechanisms of low-carbon transformation - An, Zhongyin; Xiao, Hongce; Li, Weiyi; Wang, Hengli (Frontiers in Public Health, 2025)
IntroductionThis study investigates the socioeconomic impacts of horizontal ecological compensation (HEC) policies in China, focusing on their role in mitigating environmental degradation and enhancing urban resilience.MethodsWe utilize panel data from 180 cities in the Yangtze and Yellow River basins (2007–2022) and construct an Inclusive and Resilient City (IRC) index. Policy effects are evaluated through a multi-period quasi-natural experiment.ResultsThe results indicate that HEC policies are associated with a 0.3% average increase in the IRC index, primarily driven by improvements in green innovation and industrial upgrading. These mechanisms contribute to reducing pollution-related health risks and enhance urban resilience against environmental stressors. While the average increase appears modest, it represents a meaningful improvement in urban well-being within the constraints of regional development and ecological sustainability. The robustness of these findings is confirmed through multiple tests, including parallel trend analysis and placebo tests.DiscussionThis research highlights HEC policies as an innovative policy tool that balances environmental protection with socioeconomic development. To strengthen their impact, policy optimization is recommended, aiming to further alleviate the socioeconomic burdens of environmental degradation and improve public health in urban areas.